2004
DOI: 10.1152/ajpheart.00338.2004
|View full text |Cite
|
Sign up to set email alerts
|

Opening of mitochondrial KATPchannels enhances cardioprotection through the modulation of mitochondrial matrix volume, calcium accumulation, and respiration

Abstract: Previously, we have shown that the pharmacological opening of the mitochondrial ATP-sensitive K channels with diazoxide (DZX) enhances the cardioprotection afforded by magnesium-supplemented potassium (K/Mg) cardioplegia. To determine the mechanisms involved in the cardioprotection afforded by K/Mg + DZX cardioplegia, rabbit hearts (n=24) were subjected to isolated Langendorff perfusion. Control hearts were perfused for 75 min. Global ischemia (GI) hearts were subjected to 30 min of equilibrium, 30 min of GI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…Oxygen Consumption-Mitochondrial oxygen consumption was measured using a Clark-type electrode in a liquid phase oxygen measurement system (Oxygraph, Hansatech, Norfolk, UK) (46). Complex I (state 3)-mediated oxygen consumption was initiated by the incorporation of glutamate and malate (5 mM each) to 1 ml of respiratory medium (250 mM sucrose, 5 mM KH 2 PO 4 , 5 mM MgCl 2 , 0.1 mM EDTA, and 0.1% BSA in 20 mM HEPES, pH 7.2).…”
Section: Assessment Of Mitochondrial Respiratory Function By Followinmentioning
confidence: 99%
“…Oxygen Consumption-Mitochondrial oxygen consumption was measured using a Clark-type electrode in a liquid phase oxygen measurement system (Oxygraph, Hansatech, Norfolk, UK) (46). Complex I (state 3)-mediated oxygen consumption was initiated by the incorporation of glutamate and malate (5 mM each) to 1 ml of respiratory medium (250 mM sucrose, 5 mM KH 2 PO 4 , 5 mM MgCl 2 , 0.1 mM EDTA, and 0.1% BSA in 20 mM HEPES, pH 7.2).…”
Section: Assessment Of Mitochondrial Respiratory Function By Followinmentioning
confidence: 99%
“…Also, our data regarding the effect of 5-HD are in agreement with the previous reports showing that the mK ATP blocker had no effect on the activation of the basal mitochondrial respiration by diazoxide and pinacidil applied in similar concentrations (Kopustinskiene et al 2010;Korotkov et al 2006). Furthermore, all four compounds significantly decreased State 3 respiration as was earlier demonstrated for diazoxide (Kopustinskiene et al 2002;Rousou et al 2004) and pinacidil (Kopustinskiene et al 2010).…”
Section: High-resolution Respirometrysupporting
confidence: 92%
“…13,14) It has been reported that acute inflammation causes myocardial damage, apoptosis, or necrosis and results in an intracellular and mitochondrial calcium overload similar to acute ischemia. [7][8][9][10] Therefore, a cardioprotective effect would be expected with a treatment which would reduce the calcium overload in the myocardium or its mitochondria. In the present study, we used two different clinically available K-ATP channel openers.…”
Section: Mechanisms Of the Cardioprotection Of K-atp Channel Openersmentioning
confidence: 99%
“…[3][4][5][6][7] However, K-ATP channels are found not only in the sarcolemma of myocytes, but also in the mitochondrial membrane, and openers of these mitochondrial K-ATP channels, such as nicorandil, have been proven to play an important role in its cardioprotective effect by protecting mitochondrial function, especially in short-term acute ischemia. [8][9][10] It has been reported that an increase in ventricular wall stress causes prolongation of the action potential duration, particularly in damaged myocardium with heart failure. 11) This prolongation of the action potential duration may increase transient calcium and may exaggerate intracellular calcium overload, resulting in the deterioration of myocardial dysfunction.…”
mentioning
confidence: 99%